Hormone action : basic and clinical aspects - Melmed, Shlomo (BioScientifica, 2000)
A collection of papers presented at a symposium that focused on the mechanisms of hormone action, especially that of the pituitary hormone. Intended for professional public.
HypoCCS series, ISSN 1466-4151 volume 4
Keywords: endokrinologie; Hypopituitarism; růstový hormon; hypopituitarismus; Growth Hormone; receptory somatotropinu; Receptors, Somatotropin